Efeito do estresse salino e hídrico em sementes de quinoa tratadas com GA3 - Costa, Halina Stéffany Lopes (2018)
The cultivation of quinoa (Chenopodium quinoa Willd.) Is significant because it is a species of high nutritional value and has a wide adaptation to adverse conditions. The objective of this study was to evaluate the effect of seed treatment with gibberellic acid on germination, initial seedling growth and physiological processes of quinoa, BRS Piabiru, submitted to saline and water stress. The work was carried out in four experiments. In the experiment I, the seeds were moistened with PEG 6000 and NaCl solution to simulate the effect of water and saline stress, respectively, with the solutions adjusted to 0,0; -0.2; -0.4; -0.6; -0.8; -1.0; -1,2; -1.4 and -1.6 MPa. The percentage and rate of germination, growth and dry matter accumulation of the seedlings. In experiment II, the seeds were treated in gibberellic acid at 0, 0.005, 0.010 and 0.015 mg L-1 and seeded in Petri dishes moistened with the concentrations 0,0; -0.4; -0.8; -1.2 and -1.6 MPa of PEG 6000 and NaCl. The same variables of the first experiment were evaluated. In experiment III and IV, the seeds were treated with gibberellic acid 0; 0.005; 0.010 and 0.015 mg L-1, seeded in disposable cups and cultured in 0.0 saline solution; -0.4; -0.8 MPa of NaCl in experiment III and moistened with 10%, 50% and 100% of water in field capacity in experiment IV. Growth, gas exchange, chlorophyll, and carotenoid content. The results of germination and growth of quinoa seedlings in a controlled environment were reduced with higher levels of saline stress, but the water stress was limiting to germination from -0.8 MPa. The effect of imbibition of seeds in water and gibberellic acid at 0.005 and 0.010 mg L-1 were more significant at the lower salt concentrations for germination and initial growth of quinoa. In the water stress conditions GA3 did not influence germination, but the imbibition in 0.005 and 0.010 mg L-1 of GA3 contributed to root and dry mass increase. In greenhouse, the increase of the saline concentration reduced the growth of the plants, gas exchanges and increased the concentrations of chlorophyll and carotenoids. The application of 0.015 mg L-1 of GA3 reduced leaf area and photosynthesis in the control and increased photosynthesis at salt concentrations. In water stress, quinoa growth was reduced at lower water availability, but seed treatment with GA3 minimized the effects of stress through increased gas and carotenoid changes.